الكُدية في " البخلاء" للجاحظ - يحيا مالك; الراهب سميرة; دندش سائر (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يعرض هذا البحث لظاهرة اجتماعيّة أدبيّة في المجتمع العباسيّ هي ظاهرة الكدية، وهي إحدى الطرق التي احترفها بعض بخلاء الجاحظ في سبيل تحصيل المال عن طريق الاحتيال، والمرادف لهذه الكلمة هو لفظ التسوّل، وازدادت هذه الظاهرة انتشاراً وأهمية بازدياد الفقر والحرمان، وازدياد اختلاط العرب بالعجم، إلى جانب ما يجد المُكدون فيها من طمأنينة العيش وراحة النفس. والبخيل المُكدِي كانت غايته الثراء وجمع المال، وفي سبيل الحصول على ذلك لا يتورّع عن طرق كل أبواب الاحتيال والخداع. وقد توزّع المكدون في حيلهم إلى ثلاثة أصناف: مكدون اعتمدوا على خداع حاسّة البصر، ومكدون اعتمدوا على خداع حاسّة السمع، ومكدون اعتمدوا على خداع القلوب والعقول. واخترت كتاب البخلاء للجاحظ مجالاً لعرض هذه الظاهرة؛ لأنّه كان أوّل من أدخل هذه الفئة الاجتماعية في الأدب العربيّ في القرن الثالث عبر قصصه وحكاياته، وأوّل من صنّفهم وذكر حيلهم، ومهّد الطريق لمن جاء بعده. This research discusses a literary social phenomenon in the Abbasi society, which is begging. It is one of the ways that some of the niggards in Al-Jahez’s book had mastered in order to earn money fraudulently. This phenomenon spread and gained more significance along with the increasing of poverty and deprivation, and the mingling of Arabs with foreigners. Those beggars found comfort and easiness in this lifestyle. They aimed at collecting money and becoming wealthy. In order to do so, he wouldn’t hesitate to practice all manners of deception and fraud. They can be divided into three types: beggars who use the deception of the eye, beggars who use the deception of the ear, and beggars who use the deception of the hearts and minds. And the reason I chose AL-Jahez’s The Niggards to demonstrate this phenomenon is that he was the first to deal with this social category in Arabic literature in the third century through his stories and tales. He was the first to categorize them and mention their tricks, and he paved the way to the writers after him.